The United States in the world-economy : - Agnew, John (Cambridge University Press, 1987)
First published in 1987, The United States in the World-Economy is a major textbook survey of the rise of the United States within the world-economy and the causes of its relative decline. With the USA being the dominant state in the contemporary world-economy, it is vital to understand how it got to where it is and how it responds to global economic crises. Professor Agnew emphasises the divergent experiences of different regions within the USA and in so doing provides a significant 'new' regional geography, tracing the historical evolution of the world-economy and assessing the contemporary impact of the world-economy upon and within it. No treatment prior to this work covered the subject with equivalent breadth and theoretical acuity and the guiding politico-economic framework provides a coherent radical perspective within which the author undertakes specific regional and historical analysis. The United States in the World-Economy will prove required reading for numerous courses in regional geography, area studies and the geography of the United States.